Pengaruh Earning Management Dan Mekanisme Good Corporate Governance Terhadap Pengungkapan Corporate Social Responsibility Pada Perusahaan Manufaktur Di Bursa Efek Indonesia - Kumalasari, Desi Primadita; , Zulfa Irawati, SE. MSi (2017)
This study aims to investigate the influence of Earning Management and mechanisms of Good Corporate Governance (Managerial Ownership, Institutional Ownership, Ownership Public Audit Committee, the size of the Board of Commissioners, and the proportion of BOC Independent) on the disclosure of Corporate Social Responsibility in companies listed on the Indonesia Stock Exchange period 2013-2015. The hypothesis in this study Earning Management, Managerial Ownership, Institutional Ownership, the Audit Committee is partially significant negative effect on the disclosure of Corporate Social Responsibility and Public Ownership, The size of the Board of Commissioners, Board of Independent Commissioners Proportion significant positive effect on Corporate Social Responsibility Earning Management proxied by Discretionary Accrual (DA) which is disclosed in the annual report, while CSR is proxied using the Corporate Social Responsibility Index (CSRI) that is based on a reporting standard Global Reporting Index disclosed in the company's annual report and sustainability report. Samples were selected using purposive sampling and there are 31 companies manufacturing sector and Goods Cosmetics and Pharmaceutical Customers who meet the criteria after the outliers removed. By using anaisis multiple linear regression results of the study found that in partial ownership Public, The size of the Board of Commissioners, and the proportion of BOC Independent positive effect significantly, whereas the variable Earning Management, Managerial Ownership and Institutional Ownership partially negative and not significant to the disclosure Corporate Social Responsibility. Then the Audit Committee significant influence but no negative effect. Companies should consider the main variables of Good Corporate Governance for Public ownership, size of the Board of Commissioners, Board of Independent Commissioners proportion as it affects the disclosure of Corporate Social Responsibility